2011
DOI: 10.1073/pnas.1109051108
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide poisoning is prevented by the energy costs of conformational changes in gas-binding haemproteins

Abstract: Carbon monoxide (CO) is a product of haem metabolism and organisms must evolve strategies to prevent endogenous CO poisoning of haemoproteins. We show that energy costs associated with conformational changes play a key role in preventing irreversible CO binding. AxCYTcp is a member of a family of haem proteins that form stable 5c-NO and 6c-CO complexes but do not form O 2 complexes. Structure of the AxCYTcp-CO complex at 1.25 Å resolution shows that CO binds in two conformations moderated by the extent of disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(99 citation statements)
references
References 18 publications
5
94
0
Order By: Relevance
“…In fact, the majority [e.g., cytochrome ć (PDB ID: 3ZTM) (32) Additional results of the simulated proteins are discussed in the SI Text and Figs. S11-S17.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the majority [e.g., cytochrome ć (PDB ID: 3ZTM) (32) Additional results of the simulated proteins are discussed in the SI Text and Figs. S11-S17.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that L16A binds NO on the distal face in a 6c‐NO mode (with the proximal histidine still attached) 12, without proceeding to a proximal binding mode. Consequently, this variant of cytochrome c' is a useful comparative system.…”
Section: Resultsmentioning
confidence: 98%
“…The heme environment in crystal structures of (A) ferrous A x C ytcp at 1.45 Å resolution ( PDB ID 2YLI) 12 and (B) ferrous, NO ‐bound A x C ytcp at 1.2 Å resolution ( PDB ID 2XLM) 13, with key binding‐pocket residues shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1723 The active site structure of the CO and NO bound Cyt c¤ was changed, with the orientation of the several amino-acids side chains in the binding site region altered by the presence of the exogenous ligand binding. 18,23 While the exact physiological function of the Cyt c¤ has not been elucidated, it has been suggested that Cyt c¤ may be an NO-reservoir or electron-transfer agent. The reported reduction potential of Cyt c¤ from Alcaligenes xylosoxidans (AxCyt c¤) is 184 mV vs. NHE, 16 which is lower than the reduction potential for the general cytochrome c.…”
Section: Introductionmentioning
confidence: 99%